Spatial and Single‐Cell Transcriptomics Unraveled Spatial Evolution of Papillary Thyroid Cancer - Guangzhe Zheng; Shaobo Chen; Wanqi Ma; Quanshu Wang; Li Sun; Changwen Zhang; Ge Chen; Shuping Zhang; Shuguang Chen (Advanced Science)
Abstract Recurrence and metastasis are the major issues for papillary thyroid cancer (PTC). Current morphological and molecular classification systems are not satisfied for PTC diagnosis due to lacking variant‐specific morphological criteria and high signal‐to‐noise in mutation‐based diagnosis, respectively. Importantly, intratumor heterogeneity is largely lost in current molecular classification system, which can be resolved by single cell RNA sequencing (scRNA‐seq). However, scRNA‐seq loses spatial information and morphological features. Herein, scRNA‐seq is integrated and spatially‐resolved transcriptomics (SRT) to elaborate the mechanisms underlying the spatial heterogeneity, malignancy and metastasis of PTCs by associating transcriptome and local morphology. This results demonstrated that PTC cells evolved with multiple routes, driven by the enhanced aerobic metabolism and the suppressed mRNA translation and protein synthesis and the involvement of cell–cell interaction. Two curated malignant and metastatic footprints can discriminate PTC cells from normal thyrocytes. Ferroptosis resistance contributed to PTC evolution. This results will advance the knowledge of intratumor spatial heterogeneity and evolution of PTCs at spatial and single‐cell levels, and propose better diagnostic strategy.